Membangun Karakter Antikorupsi Pada Generasi Muda Melalui Pendidikan Formal - Regita Diva Aulia; Nabila, Nabila; Rizka Julia Salsabila (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Anti-corruption education is a preventive strategy aimed at building a young generation with integrity and a strong sense of responsibility. This article explores the importance of instilling anti-corruption values from an early age through schools as a primary pillar of character education. This research employs a descriptive qualitative approach, using data collected through interviews with education experts and literature reviews from relevant journals and academic books. The findings indicate that although anti-corruption education has been integrated into the curriculum, its implementation remains challenged by factors such as the lack of exemplary role models, weak instructional methods, and the negative influence of the digital era on students’ character formation. Therefore, synergy between formal education, family, and community is essential to create an environment that consistently supports anti-corruption values as a foundation for ethical and moral development among youth.